Composite hierarchical anti-disturbance control for stochastic systems with multiple disturbances. (April 2018) - Sun, Shixiang; Wei, Xinjiang; Zhang, Huifeng
A class of stochastic systems with multiple disturbances, which includes white noises and disturbances whose time derivative is bounded, is considered in this paper. To estimate the unknown bounded disturbance, a stochastic disturbance observer is proposed. Based on the observer, a disturbance observer-based disturbance control scheme is constructed such that the composite closed-loop system is asymptotically bounded. Finally, a simulation example is given to demonstrate the feasibility and effectiveness of the proposed scheme.